2x(x+3)=x=23

Simple and best practice solution for 2x(x+3)=x=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(x+3)=x=23 equation:



2x(x+3)=x=23
We move all terms to the left:
2x(x+3)-(x)=0
We add all the numbers together, and all the variables
-1x+2x(x+3)=0
We multiply parentheses
2x^2-1x+6x=0
We add all the numbers together, and all the variables
2x^2+5x=0
a = 2; b = 5; c = 0;
Δ = b2-4ac
Δ = 52-4·2·0
Δ = 25
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{25}=5$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(5)-5}{2*2}=\frac{-10}{4} =-2+1/2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(5)+5}{2*2}=\frac{0}{4} =0 $

See similar equations:

| -10k=-60 | | x-44-x3=6 | | 186t+16=1132 | | 240+0.25=180+0.40m | | 4d+14=3(d-1) | | 2(h+3.5)=-11 | | 4y9-2y3=10 | | 170+0.15x=267.50 | | 3x-3=6-(9x+9) | | 28x-1+146=22x-3 | | 2(y-1)+y=14 | | x+(1+4x)=106 | | Y/3+y=8 | | -16(d+1)=-20 | | x10+3x5=72 | | 9-3x-1=5x+2 | | 8x-17=4x+33 | | 3x-3=6-(9x-9) | | 14s+20=-13+10s-15 | | -13=3+2k | | -25+x=5(8x-5) | | 2x–1=1–2x | | -8n=-80 | | 77+11y=77 | | 4x+5=195 | | 3j+14=4j | | 34(2m+1)=2 | | 6=84/c | | (5x+10)/(x+2)=0 | | 30=1x | | -2.3u=-0.9u+12.04 | | 25(w-2)=-2 |

Equations solver categories